Model Peningkatan Kualitas Audit Melalui Kecermatan Profesional, Kompetensi dan Etika Auditor Internal di BPKP Propinsi Riau - suharti suharti; Yusrizal Yusrizal (COSTING : Journal of Economic, Business and Accounting, 2019)
Audit quality is an inseparable part of good governance that leads to clean government. The purpose of this study was to determine the effect of Professional Accuracy, Competence and Ethics of Internal Auditors on Audit Quality. This research was conducted in BPKP Representatives of Riau Province with an auditor sample of 46 people. Data collection method is to use a questionnaire list. While the method of data analysis using multiple linear regression analysis The results of the study show that Professional Accuracy has no significant effect on Audit Quality, Auditor Quality has a significant effect on Audit Quality. Auditor Ethics has a significant effect on Audit Quality. Keywords: Audit Quality, Professional Accuracy, Competence, Ethics of Internal Auditors